(untitled) (Journal of Engineering, 2020)
The use of essential services in modern constructions, such pipes, and ducts, became important, placing these pipes and ducts underneath the soffit of the beam. They made a ceiling sandwich, and that causes to reduce the height of the floor, so the presence of the opening in the beam saves the height of the floor. In this paper, the investigation of the beam response of reinforced concrete simply supported rectangle beams with square web openings is presented, including a number of the web openings (two, four, and eight), in addition to its use in strengthening the member at the openings (when the beam is planned before casting, internal deformation steel bar is used, and in case of the opening is existing in the beam, (CFRP) fabric is used.). The test results indicated that the opening Strengthening of beams might compensate for the decrease of the beam load capacity because of the existence of the openings in the shear zone. The compensation of beam capacity depends on the strengthening method, which was adopted. The shear crack loads of the strengthened with externally CFRP specimen’s reduction ranging from (15.38 to 38.46%) of their failure loads while the shear crack load of internally reinforced strengthened ranging from (15.38 to 30.76%).